Establishing childhood cancer survivorship clinics in India: A consensus statement - Rachna Seth; Maya Prasad; Gauri Kapoor; Gargi Das; Srinivasan Prasanth; Vandana Dhamankar; Purna Kurkure; M Melissa Hudson (Elsevier, 2024)
Objectives: To provide a consensus statement describing best practices and evidence regarding the setting up Childhood Cancer Survivor Clinics in India. Methods: Key topics regarding childhood cancer survivorship clinics were identified during a workshop conducted during the annual Pediatric Hematology Oncology conference (PHOCON) in New Delhi in November 2022. Workshop participants included oncologists, hematologists, medical social workers, representatives of non-government organizations, and childhood cancer survivors. Consensus was generated by combining expert opinion and a review of the literature. Results: Several components regarding survivorship clinics, including the setting up of survivor clinics separate from the oncology clinic, the leading role of the treating oncologist in survivor clinics, the composition of survivor clinics and the patient pathways in the clinic, the frequency of follow-up for different survivors based on risk stratification, plans in adult survivors and the role of allied specialties like cardiologists, neurologists etc. were discussed. Conclusion: Care of childhood cancer survivors is complex and requires a multidisciplinary approach centred around patients and their caregivers. Addressing post-treatment concerns is critical to our patient's quality of life as survival improves. There continues to be a need to define effective and efficient programs that can coordinate this multidisciplinary effort toward survivorship.